Comunicação no pós-operatório: percepção do paciente - Jucá, Naira Maria Ferreira (1998)
The communication is part of all the activities of the man's personal relationships. It tried to analyze as the paticnt hc/she noticed the communication it equips of nursing-patient during the postoperative period, m the Room of Anesthetic Recovery. For the viabilization of this study, the quantitative abordagem was used complemented by the qualitative, so that the discoveries were apprehended and understood certanely. The interview was used open to 30 patient that the postoperative of urgêncy/emergêncv surgerv, in an emergency Hospital, in the district of Fortaleza - Ceará - Brazil, dunng the lst semester of 1997. The analysis of the data was based in the thcrapeutic communication (STEFANELLI, 1993), besidcs complementai litcrature. The data showed that of the 30 subjects, 20 were men. With relationship to the civil State, 17 were married, 12 single and a widower. It was cvidenced that most suffered accident of traffic and it was transported in private car (15) and ambulance (12). THE communication equips of nursing-patient it was noticed by the patients as having limited in the attention of yours called, for the neglet of the situations, for the disconfort, absence of the family and for anything to know about íts condition of health and of disease. In spite of her to have identified in the recovery room a demand that exceeds the possibilitics of the nursing team to provide an attendance with quality, he/she makes himself necessarv a wider undcrstanding about the communication in the process of taking care in nursing.